2005
DOI: 10.1124/mol.105.017210
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Profiling of Orthochirus scrobiculosus Toxin 1 Analogs with a Trimmed N-Terminal Domain

Abstract: channel affinity and selectivity. Whereas the affinity to Kv1.1 and Kv1.3 did not change significantly, the affinity to Kv1.2 and K Ca 3.1 was drastically reduced with the truncations. It is surprising that a striking gain in potency was observed for Kv3.2. In contrast, a truncation of the C-terminal domain, expected to partially disrupt the toxin ␤-sheet structure, resulted in a significant decrease or a complete loss of activity on all channel types tested. These data highlight the value of structurefunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 25 publications
3
35
0
Order By: Relevance
“…AbNaTx6, AbNaTx9 and AbNaTx10 display 64%, 63% and 60% sequence identities to BmKAEP, an anti-epilepsy peptide from M. martensii Karsch [77,78], respectively, suggesting that the three peptides may also have activities inhibiting epilepsy. AbTx9 shows 95%, 79% and 74% sequence identities with Kaliotoxin-1, OSK1 and ADWX-1, the three potent blockers of the Kv1.3 channel [79][80][81], respectively. It was shown that Kv1.3 is a therapeutic target for T cell-mediated autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…AbNaTx6, AbNaTx9 and AbNaTx10 display 64%, 63% and 60% sequence identities to BmKAEP, an anti-epilepsy peptide from M. martensii Karsch [77,78], respectively, suggesting that the three peptides may also have activities inhibiting epilepsy. AbTx9 shows 95%, 79% and 74% sequence identities with Kaliotoxin-1, OSK1 and ADWX-1, the three potent blockers of the Kv1.3 channel [79][80][81], respectively. It was shown that Kv1.3 is a therapeutic target for T cell-mediated autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…potency, such as scorpion toxins charybodotoxin (ChTX), OSK1, BmKTX and their analogs [3][4][5], and sea anemone toxin ShK and its derivatives [6]. Recently, scorpion Kunitz-type toxins were also found to block Kv1.3 channel [7].…”
Section: Introductionmentioning
confidence: 99%
“…In past years, many peptides isolated from various animal venoms could potently inhibit Kv1.3 channels. These toxins usually had 30 -40 residues cross-linked by three disulfide bridges, such as Odk2, KTX, OSK1, AOSK1, HsTx1, and ShK (7)(8)(9)(10). Until now, the screening and design of novel potent and selective Kv1.3 inhibitors derived from animal toxins remain an attractive prospect for disease diagnosis and treatment (11)(12)(13).…”
mentioning
confidence: 99%